Brown Recluse Spider, Loxosceles reclusa Gertsch and Mulaik (Arachnida: Araneae: Loxoscelidae) - Howard V. Weems, Jr.; W. H. Whitcomb (EDIS)
This document is EENY-233 (originally published as DPI Entomology Circular 158), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: August 2001. Revised: October 2002.